Implementing resisted and unresisted sprint training across multiple sports : practical guidelines and considerations - Zabaloy, Santiago (2025)
Given the critical importance of sprinting, particularly its role in performance enhancement (e.g., acceleration capacity and maximal sprint speed during decisive actions) and injury prevention (e.g., hamstring protection), this article provides an up-to-date, informed perspective on the topic. To improve sprint performance, coaches and practitioners commonly employ a variety of training strategies, including “unresisted sprint training” (UST; i.e., a primary training method that directly replicates sprinting technique, such as a traditional sprint effort) and “resisted sprint training” (RST; i.e., a secondary training method involving, for example, sprint drills executed with added resistance, thereby modifying sprinting technique). Although both approaches have shown promising results, the optimal loading magnitude for applying RST remains a topic of debate, especially when using sled-towing or weighted vests. Nevertheless, enhancing sprint performance continues to represent a fundamental objective in athletic development, and training methodologies should be strategically planned through appropriate load management and intensity guidelines to elicit the specific adaptations required to optimise performance across distinct individual and team sport contexts. This narrative review and perspective article aims to provide practitioners with a critical analysis of the current evidence on the acute and chronic effects of UST and RST using sled-towing and weighted vests in elite athletes from different sports, together with practical recommendations (e.g., load prescription schemes, sprint distance adjustments, and recovery interval management) to optimise sprint performance.